Gambaran Kadar Kolesterol-LDL (Low Density Lipoprotein) Sebelum dan 48 Jam Sesudah Melakukan Satu Kali Terapi Bekam Basah Pada Penderita Hipertensi Dengan Pola lima titik - Suryanta, Suryanta; Septiana, Winda (Jurnal Teknologi Laboratorium, 2016)
Hypertension, or more commonly known as high blood pressure is a condition in which a person got an increasing blood pressure upper normal, resulting in increasing morbidity and mortality. The long hypertension is one risk factor for cardiovascular disease, which is one cause of atherosclerosis. Atherosclerosis is a very progressive diseases that causes hardening of the arteries due to the blockage by oxidized cholesterol. Atherosclerosis begins with the build up of LDL-cholesterol. There are two handling of LDL-cholesterol; pharmacological and non-pharmacological. Nonpharmacologic is done with wet cupping therapy. The aim of this study is to determine the average LDL-cholesterol levels before and after the wet cupping therapy with five-point pattern. This research is descriptive research, then presented in the form of tables to showing the results of the study. This study was done Talunombo, Sidomulya, Pengasih, Kulon Progo. This research object is venous blood samples taken from hypertensive patients as research subjects. Descriptive test results obtained an average LDL-cholesterol levels before the wet cupping therapy is 114,182 mg/dl and after wet cupping is 115,618 mg/dl. The conclusion of this study is the average LDL-cholesterol levels prior to the wet cupping therapy with a five-point pattern is 114,182 mg/dl and after wet cupping with five-point pattern is 115,618 mg/dl.